2014
DOI: 10.1007/s10668-014-9559-0
|View full text |Cite
|
Sign up to set email alerts
|

Remittances in the face of disasters: a case study of rural Samoa

Abstract: In Samoa, like in most Small Island Developing States, remittances are important to sustain people's daily livelihood and become even more significant in the face of disasters. This study investigates the role of remittances in households' response to disasters. The focus is on Samoa, where participatory activities and interviews were carried out in coastal communities affected by the tsunami of 2009, and some of which were further hit by cyclone Evan in 2012. It is found that remittances are very fast in reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…These incidental findings correspond with the more systematic findings of Le De et al () who analysed remittances to Samoa following the tsunami on 29 September 2009. Le De et al () reviewed monthly remittance data and found that the monthly remittance pattern for the disaster year (2009) mirrored exactly the average monthly remittance pattern in non‐disaster years (2006–08) except for two months after the tsunami.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…These incidental findings correspond with the more systematic findings of Le De et al () who analysed remittances to Samoa following the tsunami on 29 September 2009. Le De et al () reviewed monthly remittance data and found that the monthly remittance pattern for the disaster year (2009) mirrored exactly the average monthly remittance pattern in non‐disaster years (2006–08) except for two months after the tsunami.…”
Section: Introductionsupporting
confidence: 89%
“…These incidental findings correspond with the more systematic findings of Le De et al () who analysed remittances to Samoa following the tsunami on 29 September 2009. Le De et al () reviewed monthly remittance data and found that the monthly remittance pattern for the disaster year (2009) mirrored exactly the average monthly remittance pattern in non‐disaster years (2006–08) except for two months after the tsunami. When affected households were asked to rate the significance of remittances to them over a one‐year period (one month before the tsunami and 11 months after it), the significance of remittances rose to a 9 out of 10 rating for two months post disaster and fell steadily to 3 out of 10 by the end of the year.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although far from being exclusively created externally, vulnerabilities are often imposed from outside [11][12][13] with little notice and little opportunity to counter them. Conversely, resiliences are not exclusively an intra-community matter, because national and international support systems are frequently assumed to exist and to be an inevitable part of a community dealing with disaster, such as remittances [61] and national social safety nets. V2R and IFRC's resilient community characteristics will not necessarily capture all such dimensions, depending how extensive the work is.…”
Section: Critical Reflectionmentioning
confidence: 99%